Assessment of High-Power Catheter Ablation in Patients With Atrial Fibrillation: A Meta-Analysis - Mao, Zhi-Jie; Pei, Yan; Lin, Hui; Xiang, Yin; Huang, Zhou-Qing; Xiao, Fang-Yi; Chen, Yi-He (Frontiers in Cardiovascular Medicine, 2021)
Background: High-power radiofrequency (RF) catheter ablation was considered as a promising alternative strategy to conventional-power ablation in the treatment of patients with atrial fibrillation (AF). This study sought to compare the efficacy and safety of high-power energy delivery to that of conventional-power setting in AF catheter ablation. Methods: We performed a systematic review of relevant literature in Pubmed, Embase, Cochrane library, and Google Scholar database. Sixteen eligible studies totaling 3,307 patients (1,929 for high-power ablation; 1,378 for conventional-power ablation) met inclusion criteria. Results: During a median 12 month follow-up, high-power ablation showed a significantly higher AF/atrial tachycardia-free survival rate in comparison with conventional-power ablation (risk ratio [RR] 1.09, 95% CI 1.02 to 1.15, p = 0.008). Notably, a high-power strategy convincingly decreased the procedure time (weighted mean difference [WMD] −46.11 min, 95% CI −59.15 to −33.07, p < 0.001) and RF ablation time (WMD −19.19 min, 95% CI −24.47 to −13.90, p < 0.001), along with reduced fluoroscopy time (WMD −7.82 min, 95% CI −15.13 to −0.68, p = 0.036). In addition, there was no perceptible difference in the potential risk of procedure-related complications between these two approaches (RR 0.81, 95% CI 0.48 to 1.37, p = 0.428). Conclusions: High-power RF catheter ablation was associated with an improvement in long-term sinus rhythm maintenance for treatment of AF, without exacerbating the risk of adverse events during the procedure. Impressively, high-power pulmonary vein isolation had the potential to shorten the application duration and minimize fluoroscopic exposure.